Efeito anti-inflamatório do extrato etanólico da Harpagophytum procumbens durante a inflamação intestinal de camundongos infectados com Salmonella Enteritidis (ATCC13076) - Bisinotto, Rosalia do Carmo (Universidade Federal de São Carlos, 2014)
Salmonellosis is an illness caused by bacteria of the genus Salmonella, a leading infectious disease worldwide. Due to the importance of this infection forward to eating habits, the search for a new compound that can contribute to current therapy against intestinal inflammation caused by Salmonellosis is of great value. The goal of this research was evaluate of this treatment effect with extract of Harpagophytum procumbens ( Hp ) in murine intestinal salmonellosis . In this research were realized counting of total cells and differential cell ( leukocytes, neutrophils and mononuclear cells) , dosages of cytokines (TNF- α , IL-12 , IL-10 and IL-4 ) and histopathological analysis of the liver and small intestine, at third and seventh day after the infection on animals treated with Hp and with animals didn t treated with. The animals were divided in: infected ( SE ) , infected and treated with Hp ( SE + HP ) and control group( C ). Balb / c mice ( female) were infected ( v.o ) with S. Enteritidis ATCC 13076 ( 1x108 UFC - 100 mL / animal) . The SE + HP group was treated with 150 mg / animal daily with Hp . The pathology of the liver and small intestine was prepared and stained with HE. Our results showed that there was an increase of leukocytes, specifically mononuclear cells analyzed in different compartments ( blood and CSF ), increased neutrophils in the blood in animals infected with SE on day 7 after infection. However, treatment with Hp was able to down modulate the recruitment of mononuclear cells on day 7 into the peritoneal cavity and negatively modulates the number of neutrophils in the same period. The levels of TNF-α showed a decrease on day 7 after treatment with Hp, suggesting a biological effect - down regulation - the inflammatory process in these animals . Furthermore, we also observed that animals treated with Hp infected with SE had a reduction in the number of neutrophils and mononuclear cells in the blood and decrease of IL -12. The production of IL-4 showed an increase in the + SE group HP suggesting that animals infected with S. Enteretidis and treated with H. procumbens appears to favor a microenvironment that directs the immune response profile of Th2 to Th1, whereas IL- 12 showed a decrease. IL- 10 has important regulatory effects on immunological and inflammatory responses mediated predominantly by macrophages. Our results show an increase of IL-10 in animals infected with SE, and this increase seems to be related to the severity of salmonellosis. Treatment with Hp stimulated inhibitory activity of IL - 10, favoring slight inhibition of the inflammatory process, on day 7 after infection. In the histopathological analysis of the liver observed that there was no difference between the groups, suggesting a local infection, since the blood culture was negative, carrying no systemic infection. In the small intestine was observed after 72 h in the SE group discrete wrinkle this epithelium, suggesting the invasion of S. Enteritidis, which was also observed hypertrophy of the wall of the villi and mild inflammatory infiltrate. In animals that received treatment with Hp hypertrophy was reduced with preservation of the villi of the intestinal architecture 7 days after infection. Thus, we suggest a possible role of Hp in modulating immune factors involved in the recruitment of inflammatory cells in the intestine of animals infected with SE, favoring discrete modulation of the inflammatory process in this model.
Keywords: Biotecnologia; Harpagophytum procumbens; Salmonelose; Salmonella Enteritides; Atividade antiinflamatória; Interleucina; Harpagophytum procumbens; Salmonellosis; Salmonella enteritides, Anti-inflammatory activity; Interleukin; OUTROS